Execution of Fiduciary Guarantees Post Constitutional Court Decision Number 18/PUU-XVII/2019 According to Legal Justice Theory - Umami, Allan Mustafa; Alwajdi, Muhammad Farid (JUPE : Jurnal Pendidikan Mandala, 2024)
Execution of fiduciary guarantees is a right for creditors holding fiduciary guarantees. The condition for a creditor to be able to execute a fiduciary guarantee is that the breach of promise of the debtor providing the fiduciary guarantee is fulfilled. According to Article 19 of Law Number 42 of 1999 concerning Fiduciary Guarantees (Fiduciary Law), creditors can execute objects that become fiduciary collateral if the debtor providing the fiduciary guarantee defaults. However, the creditor's rights above are not in accordance with other regulations because execution cannot simply be carried out. To carry out execution, the creditor must submit an application to the District Court. It should be understood that the birth of this fiduciary guarantee is to streamline the economic system, namely to make it easier for people to obtain financing for the purchase of movable objects without having to place the objects purchased as collateral in a financing institution. The debtor can still use the movable object in the hope that it will be used to improve the debtor's economy. This reality in the field is also confirmed by the decision of the Constitutional Court (MK) Number 18/PUU-XVII/2019 which interprets Article 15 of the Fiduciary Law which essentially states that the execution of fiduciary guarantees must carry out a request for execution in the District Court. The formulation of the problem in this research is 1. What is the law on voluntary execution of fiduciary guarantees in Indonesia? 2. What is the impact of the Constitutional Court (MK) decision Number 18/PUU-XVII/2019 on the protection of creditors holding fiduciary guarantees according to the theory of legal justice? This legal research method is normative legal research using a statutory regulation approach. The result of this research is the implementation of post-judgment fiduciary guarantee execution No.18/PUU-XVII/2019 has not provided legal certainty that provides justice because there are still differences in interpretation regarding fiduciary guarantees.